Using a 308-nm excimer laser to treat vitiligo in Asians - Al-Otaibi, Sultan R. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
BACKGROUND: Current vitiligo therapies require many months of treatment and often result in disappointing outcomes. Treatment with a 308-nm excimer laser has shown promising results in patients with vitiligo. OBJECTIVE: This controlled prospective trial studied the effectiveness of the 308-nm excimer laser for treating vitiligo in Asians. METHODS: Thirty-four patients (14 males and 20 females) with localized vitiligo were enrolled in the study. Vitiligo patches were treated using a 308-nm excimer laser. Lesions were treated twice weekly for 13 weeks. The treatment was started with 50 to 100 mJ/cm2 (according to site) and increased by 50 mJ/cm2 in every session until erythema appeared. Patients were treated for 25 sessions, or until 100% repigmentation, whichever was achieved first. The overall response rate was assessed clinically and by comparison of photographs before and after treatment by two independent investigators. RESULTS: Twenty-nine patients (12 males and 17 females) completed the study. Lesions on the face responded better than elsewhere on the body. The least responsive areas were the hands and feet. The average number of treatment sessions prior to repigmentation was 11. Untreated control patches remained unchanged. In higher skin phototypesthe response was more favorable. There was no significant correlation between the age of the patients and their response to treatment. CONCLUSION: The use of the 308-nm excimer laser for the treatment of vitiligo is effective, relatively safe, and more convenient compared to other available modalities of treatment for stable vitiligo with small patches. However, similar to other modalities of treatment, the therapeutic effect is mainly dependent on the location of vitiligo lesions.
Keywords: Adult; Aged; Aged, 80 And Over; Child; Child, Preschool; Ethnology; Follow-Up Studies; Kuvajt; Kuwait; Odrasli; Otrok; Otrok predšolski; Pathology; Prospective Studies; Prospektivne študije; Radiotherapy; Sledilne študije; Starost 80 in več; Starostniki; Treatment Outcome; Vitiligo; Zdravljenje, izid